Chrześcijańska perspektywa rozwiązywania kwestii społeczno-ekonomicznych w świetle nauczania Jana Pawła II i założeń personalizmu G.M. Gronbachera - Twardowski, ks. Mirosław (Annales. Etyka w Życiu Gospodarczym, 2015)
In this essay I would like to outline the Christian perspective on solving economicissues based on documents of the Catholic Church. The term ‘economic personalism’appeared in literature several years ago and has been used as a proposal ofa new economic model which is supposed to be a synthesis of achievements ofeconomic sciences and Christian moral theology. Pope John Paul II is believed tobe one of its precursors or even founding-fathers. We shall sum up these significantelements of papal personalism under the following heads: (1) A man isa person, namely an independent existence in material and personal, spiritual andmaterial sense, rational and free. All these characteristics of a human being constitutea basis for his dignity and greatness; (2) A man is a free being. This meansthat he has to make choices between various values. Human freedom is closelyrelated to the truth. The final objective of human freedom is love; (3) We canprotect ourselves against alienation by acting and being together with others. Wewill avoid the danger of alienation when we make ourselves a gift for the otherperson and especially for God.Economic personalism develops John Paul II’s personalistic view in a creativeway. Its program can be summarized by the following theses: (1) a man is thecentre of economy; (2) a human being is the most important economic good; (3)work is part of the man’s calling; (4) reproducibility of goods is subordinated tothe man’s integral development; (5) the right to participate constitutes inalienablehuman right; (6) the principle of subsidiary is an „intellectual” frame for socialand economic order; (7) the market should not be absolutized; (8) solidarity withthe poor and social justice constitute a basis of each economy.